Total Pharyngo-esophageal Stenosis: A New Surgical Procedure Using Modified Retrograde Transillumination Approach - Lechien, Jerome R; Dapri, Giovanni; Saussez, Sven (Surgical laparoscopy, endoscopy & percutaneous techniques, 2018)
We performed a modified combined anterograde-retrograde dilatation in a 60-year-old woman with complete pharyngo-esophageal stricture (PES). With a large endoscopic view from the upper (laryngoscope) and lower (pediatric gastroscope introduced via gastrostomy tube) parts of the PES, the approach consisted of a retrograde puncture of the complete PES by transillumination to take the guide coming from the pediatric endoscope. The guide was pulled through the mouth and the PES dilatation was made using successive boogies of various diameters through the guide. Finally, a salivary bypass was placed to maintain the diameter of the pharyngo-esophageal way. The surgical approach was performed in 25 minutes without short, medium, and long-term complications. The patient started oral alimentation the day after the surgery, and the salivary bypass was removed after 6 months. The subject had no recurrence of the PES at 5 years.